Recent Advances in Diagnosis and Treatment of Infectious Uveitis Prevalent in Asia-Pacific Region. Issue 1 (January 2021) - Patel, Anamika; Kelgaonkar, Anup; Kaza, Hrishikesh; Tyagi, Mudit; Murthy, Somasheila; Pathengay, Avinash; Basu, Soumyava
Abstract : Abstract: The role of infections in intraocular inflammation is being increasingly recognized across the world. The Asia-Pacific region, being the single largest and most populous geographical entity on the planet, is home to a wide variety of such infections. Not surprisingly, there has been an explosion in the literature on infectious uveitis emerging from Asia-Pacific countries. In this review, we have covered recent advances in the diagnosis, treatment, and pathogenesis of common forms of infectious uveitis from the Asia-Pacific region. Much of the literature is focussed on the diagnosis of these infections by clinical criteria and laboratory investigations. There has also been an increased emphasis on the application of newer modes of ocular imaging and understanding pathomechanisms of ocular inflammation in these infections. Together this research has significantly improved our understanding of the diagnosis and management of infectious uveitis.